2012
DOI: 10.1016/j.canep.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with inadequate colorectal cancer screening with flexible sigmoidoscopy

Abstract: Background and study aim Inadequate colorectal cancer screening wastes limited endoscopic resources. We examined patients factors associated with inadequate flexible sigmoidoscopy (FSG) screening at baseline screening and repeat screening 3–5 years later in 10 geographically-dispersed screening centers participating in the ongoing Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial Methods A total of 64,554 participants (aged 55 – 74) completed baseline questionnaires and underwent FSG at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…71 Most studies were in individuals aged ≥50 [70][71][72] or ≥55 years. 68,69,73 The sensitivity of FS depends on the adequacy of mucosal inspection and is operator-dependent. 73 Studies have shown inadequate screening in up to 91.7% of cases, ie <50 cm depth of insertion.…”
Section: Flexible Sigmoidoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…71 Most studies were in individuals aged ≥50 [70][71][72] or ≥55 years. 68,69,73 The sensitivity of FS depends on the adequacy of mucosal inspection and is operator-dependent. 73 Studies have shown inadequate screening in up to 91.7% of cases, ie <50 cm depth of insertion.…”
Section: Flexible Sigmoidoscopymentioning
confidence: 99%
“…68,69,73 The sensitivity of FS depends on the adequacy of mucosal inspection and is operator-dependent. 73 Studies have shown inadequate screening in up to 91.7% of cases, ie <50 cm depth of insertion. 73 The technique had relatively low and fluctuating participation rates (20.9%-63.0%).…”
Section: Flexible Sigmoidoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Black study subjects, unmarried persons and those with less than a high school education were less likely to return for repeat examinations [59]. Those with inadequate FS at baseline were also less likely to return for a repeat examination when compared with those with adequate baseline FS (65.3 vs 81.6%; p < 0.001) [60]. …”
Section: The Challenges After Fs Examinationsmentioning
confidence: 99%
“…These patients are usually rescheduled for a repeat examination in usual clinical practice. Factors that have been identified as associated with an increased risk of inadequate FS include advancing age, female sex and cigarette smoking, but obesity was associated with a reduced risk [60-62]. Inadequate FS dampens the enthusiasm of patients for further endoscopic screening.…”
Section: The Challenges After Fs Examinationsmentioning
confidence: 99%